Mental disorders in northeastern Brazil: variations and disparities of mortality and morbidity from 2007 to 2016 - Carina Taíse de Medeiros Macêdo; Fábia Barbosa de Andrade (O Mundo da Saúde, 2020)
Mental disorders have increased in recent years, having a major impact on the quality of life of Northeastern Brazilians. From the point of view of health problems in society, mood disorders and other mental and behavioral disorders are currently considered to be major public health problems. Thus, the present study aimed to evaluate the morbidity and mortality indicators in the Northeast region of Brazil in relation to mood disorders and other mental and behavioral disorders in the period from 2007 to 2016 in northeastern Brazil. This is a retrospective, exploratory study, which used information from northeastern Brazil, produced by DATASUS. The dependent variable was the morbidity and mortality rate, and the age range, sex, education, and marital status were considered independent variables, considering a 95% confidence interval. It was found that the average mortality rate of both diseases showed a general decreasing tendency; however, there were some points of increase, such as in the period between 2007 and 2008 for other mental and behavioral disorders as well as between 2009 and 2010 for mood disorders. The data indicated that the most vulnerable populations are children and the elderly, as well as an increase in the use of alcohol. This makes adjusting and restructuring health actions to prevent mental illness indispensable, through the strengthening of substitute services and Primary Care for receiving users of the community.